2017
DOI: 10.1142/s021974991740007x
|View full text |Cite
|
Sign up to set email alerts
|

Geometrical structures for classical and quantum probability spaces

Abstract: On the affine space containing the space S of quantum states of finitedimensional systems there are contravariant tensor fields by means of which it is possible to define Hamiltonian and gradient vector fields encoding relevant geometrical properties of S. Guided by Dirac's analogy principle, we will use them as inspiration to define contravariant tensor fields, Hamiltonian and gradient vector fields on the affine space containing the space of fair probability distributions on a finite sample space and analyse… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…We will now exploit the Jordan–Lie-algebra structure of introduced above to obtain geometric tensor fields on , specifically, we obtain a symmetric, contravariant bivector field associated with the Jordan product , and a Poisson bivector field associated with the Lie product on . This is the generalization to a generic (finite-dimensional) -algebra of what is done in [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] for the specific case for a finite-dimensional Hilbert space . Then, we will show how the manifolds of positive linear functionals introduced in the previous section may be interpreted as a sort of analogs of symplectic leaves for the symmetric tensor in a sense that will be specified later.…”
Section: From the Jordan Product To Riemannian Geometriesmentioning
confidence: 99%
See 2 more Smart Citations
“…We will now exploit the Jordan–Lie-algebra structure of introduced above to obtain geometric tensor fields on , specifically, we obtain a symmetric, contravariant bivector field associated with the Jordan product , and a Poisson bivector field associated with the Lie product on . This is the generalization to a generic (finite-dimensional) -algebra of what is done in [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ] for the specific case for a finite-dimensional Hilbert space . Then, we will show how the manifolds of positive linear functionals introduced in the previous section may be interpreted as a sort of analogs of symplectic leaves for the symmetric tensor in a sense that will be specified later.…”
Section: From the Jordan Product To Riemannian Geometriesmentioning
confidence: 99%
“…If for some finite-dimensional Hilbert space , it is a matter of direct inspection to show that tensor fields and defined above coincide with those introduced in [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: From the Jordan Product To Riemannian Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…This metric in a mathematical context corresponds to the Fubini-Study metric [4,5], and it has been extensively studied in the field of quantum information theory, see for instance [6,7]. Furthermore, in recent years, a lot of work has been done in order to understand the role that information theory plays in Quantum Mechanics, and it has been found that within this theory there is a rich geometric structure [3,8,9,10,11], where play role several structures. One of these approaches consists in defining the Quantum Geometric Tensor (QGT) of the parameter space of the system [3].…”
Section: Introductionmentioning
confidence: 99%
“…Information geometry on the quantum state space is of great importance from geometrical understanding of quantum theory as well as pure mathematical interest [1][2][3][4][5][6][7][8]. Indeed, the success of geometrical description of quantum theory in various problems should be stressed [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%